Women's satisfaction with quality of prenatal care services at selected barangay health centers in Imus, Cavite - Urbano, Ryan Joseph Punsalan (Animo Repository, 1999)
This study seeks to answer the degree of satisfaction of women with the quality of prenatal care services received at the selected barangay health centers and the factors associated with the women's degree of satisfaction.The study was conducted in barangays Tanzang Luma, Bahayang Pag-Asa, Medicion I and Medicion II in the municipality of Imus, Cavite. It covered four (4) barangay health centers and sixty (60) pregnant women. Face-to-face exit interviews with pregnant women were made and data were analyzed using quantitative tools.The findings of the study revealed that majority of the women who acknowledged receipt of these services were satisfied with the quality of care received, specifically, on interpersonal relations, access to services and continuity mechanisms existent at the health facilities. Women's assessment of and satisfaction with the quality or prenatal care services are associated not by their personal attributes but rather by the structural and process elements of prenatal care present in the health facilities. The structural elements of prenatal care include amenities and accessibility features of the service delivery points while interpersonal relations, perceived competence of the health providers, information given to clients and continuity mechanisms comprise the process elements of prenatal care.